2009
DOI: 10.1016/j.cellbi.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

N‐Nitrosopiperidine and N‐Nitrosodibutylamine induce apoptosis in HepG2 cells via the caspase dependent pathway

Abstract: The human hepatoma cell line (HepG2) exhibited a dose and time-dependent apoptotic response following treatment with N-Nitrosopiperidine (NPIP) and N-Nitrosodibutylamine (NDBA), two recognized human carcinogens. Our results showed a significant apoptotic cell death (95%) after 24h treatment with NDBA (3.5 mM), whereas it was necessary to use high doses of NPIP (45 mM) to obtain a similar percentage of apoptotic cells (86%). In addition, both extrinsic (caspase-8) and intrinsic pathway (caspase-9) could be impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…Moreover, alterations in the redox status of the cell to a more oxidizing environment occurs prior to the final phase of caspase activation in many model of apoptosis (Susin et al, 1998;Morel and Barouki, 1999). Thus, the results obtained in our recent works, where NPIP and NDBA can also cause ROS production in human leukemia (HL-60) and human hepatoma (HepG2) cell lines García et al, 2009), were found to be innovative.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Moreover, alterations in the redox status of the cell to a more oxidizing environment occurs prior to the final phase of caspase activation in many model of apoptosis (Susin et al, 1998;Morel and Barouki, 1999). Thus, the results obtained in our recent works, where NPIP and NDBA can also cause ROS production in human leukemia (HL-60) and human hepatoma (HepG2) cell lines García et al, 2009), were found to be innovative.…”
Section: Introductionmentioning
confidence: 70%
“…For these experiments, HL-60 and HepG2 cells were cultured in RPMI 1640 Medium and Dulbecco's Modified Eagle's Medium, respectively, without phenol red and without fetal calf serum and subsequently were pre-incubated with vitamin C (5, 10 and 50 μM), DADS or DPDS (1, 2.5 and 5 μM) for 1 h. Significant ROS levels were detected after treatment with 20 and 25 mM NPIP in HL-60 and HepG2 cells, respectively, whereas NDBA (2 mM) only induced ROS production in HL-60 cells García et al, 2009). Consequently, we did not examine the effect of vitamin C, DADS or DPDS on NDBA-induced ROS production in HepG2 cells.…”
Section: Measurement Of Rosmentioning
confidence: 98%
See 3 more Smart Citations